Pengelolaan Museum Negeri Siginjei Provinsi Jambi Sebagai Daya Tarik Wisata - Indra Eftritianto, M Rian; Wardi, I Nyoman; Bawono, Rochtri Agung (Humanis, 2020)
Indonesian Museum was formed by European aristocrats who like to collect ancient objects during the Dutch colonialism, which is useful for preserving, fostering, and developing culture by tracing Indonesian culture. Starting from this, the Van Het Bataviaasch Genootschap Kunsten Wetenschappen Museum was founded on April 24, 1778 which was the first museum in the Indonesian Museum. Museum collections and cultural preservation objects must collaborate with other fields of science such as technology, geography, and history. The museum collection objects in Indonesia can be broadly divided into two types, namely general museums and special museums. The objective to be achieved in this research is to know the strategy of managing the Siginjei State Museum of Jambi Province as a tourist attraction in developing tourism in Jambi Province. The problem of Human Resources (HR) how to overcome it is by including the staff and employees of the Siginjei State Museum of Jambi Province in research and education about museums and foreign language courses. Based on the percentage obtained, 40.20% of respondents were in the number disagreeing with the total number of 725 who chose the category of disagreeing with some of the questions given, while 43.20% were in the number agreeing with the total number of 779 respondents. This percentage can be assumed that many visitors agreed with the management of the museum management and the condition of the Siginjei State Museum of Jambi Province itself.